The Geylang's Dual Face: The Interaction of Night Tourism and Community - Dananjaya, Ahmad Ghazy (International Journal of Sustainable Competitiveness on Tourism, 2026)
Geylang presents a fascinating dual face: often stereotyped as a "red-light district," it simultaneously thrives as a vibrant urban enclave rich in history, culture, and dynamic community life. This study investigates the complex interaction between its evolving night tourism landscape and efforts in Community-Based Tourism (CBT). We highlight the inherent opportunities and significant challenges, particularly concerning equitable benefit redistribution and preserving local identity amidst transformation. Despite the persistent stigma, actual illegal activities have drastically declined due to law enforcement efforts and strategic urban development initiatives, though public perception lags. The research identifies tension between centrally planned commercialization efforts and bottom-up community initiatives like the Geylang Serai Cultural Belt, which safeguard Malay heritage. While Geylang's immense CBT potential is evident in its cultural tours and local involvement, transparent mechanisms for direct financial benefits to the broader community are lacking, risking cultural commodification. Its "gritty" night tourism, offering authentic street food and bazaars, faces the challenge of diversifying without sacrificing its unique charm. Based on qualitative fieldwork in May 2025, this study concludes that Geylang's future necessitates a careful balance, fostering economic growth and image rebranding while mitigating gentrification and ensuring tourism genuinely empowers local communities and preserves its distinct character.